Detraining effect on sprint swimming performance and load-velocity profile - Ruiz-Navarro, J. J.; López-Belmonte, Ó.; Febles-Castro, A.; Gay, A.; López-Contreras, G.; Morales-Ortiz, E.; Arellano, R. (International Journal of Sports Physiology and Performance, 2025)
Purpose: To assess the effect of 5-week training-cessation period on performance and load-velocity profile-related variables.